OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY FEATURES OF FOCAL CHOROIDAL EXCAVATION AND THE CHOROIDAL STROMA VARIATIONS WITH OCCURRENCE OF EXCAVATION. Issue 12 (December 2020) - Rajabian, Firuzeh; Arrigo, Alessandro; Jampol, Lee M.; Mercuri, Stefano; Introini, Ugo; Bandello, Francesco; Battaglia Parodi, Maurizio
Abstract : Purpose: To describe retinal and choroidal vascular changes, and choroidal stroma variations occurring in focal choroidal excavation (FCE). Methods: Study design was a cross-sectional case series. Consecutive patients affected by FCE and healthy controls were recruited. All patients underwent complete ophthalmologic assessment and multimodal imaging, including structural optical coherence tomography and optical coherence tomography angiography. Choroidal thickness and stromal index were calculated from structural optical coherence tomography images. Moreover, we measured vessel density values of the superficial capillary plexus, deep capillary plexus and choriocapillaris at the level of the macula. Results: Twenty-two patients (28 eyes; mean age 57.2 ± 16.4) and 28 control eyes (mean age of 56.5 ± 9.8) were included. Five patients (23%) were asymptomatic, whereas 17 patients (77%) complained of visual symptoms. FCE was associated with choroidal neovascularization in 10 eyes (35%). Choroidal stromal component was lower in FCE patients than controls, whereas choroidal thickness was unremarkable. Stromal index values calculated in the region proximal to the FCE was significantly lower than the values obtained from the external region. Deep capillary plexus vessel density was lower in FCE than controls. Choriocapillaris was altered in the region surrounding the FCE, whereas it was normal in the external region. Conclusion: Deep capillary plexus and choriocapillaris plexus were significantly altered in FCE patients. Moreover, choroidal stroma was significantly reduced in the areas closer to FCE compared to the surrounding choroid in patients, as well as compared to healthy controls, suggesting the hypothesis of weakening of the architectural support, creating a more friable point, which can favor FCE development. Abstract : This study describes retinal and choroidal vascular changes and choroidal stroma variations occurring in focal choroidal excavation. Vascular plexa resulted altered in focal choroidal excavation patients. Moreover, the reduced choroidal stromal index suggested the hypothesis of weakening of the architectural support, creating a more friable point, which can favor focal choroidal excavation development.